Clément Marot and religion : a reassessment in the light of his Psalm paraphrases - Wursten, Dick (Brill's series in church history ;, 2010)
A far-reaching analysis of Clément Marot's poetry (mainly his Psalm paraphrases) shows that this poet was much more than a frivolous court poet; he was touched by the humanist yearning to restore old texts (in this case the Jewish Psalter) to their original glory. In his translations he was inspired by Martin Bucer's Commentary.